MOLECULAR DOCKING AND DFT STUDIES OF COMPOUNDS IDENTIFIED FROM BARLERIA CRISTATA LEAVES TO RHEUMATOID ARTHRITIS PROTEIN - J. IRSHAD AHAMED; ABIRAMI KANDHASWAMY; K. S. MEENA (International Journal of Pharma and Bio Sciences, 2017)
Barleria plant of family Acanthaceae is used traditionally for a wide variety of biomedical properties such as anemia, toothache, cough, hypoglycemic agent, anti inflammatory agent. Owing to the multiple pharmacological properties, the compounds were investigated for the treatment of autoimmune disorders by in silico approach. Phytochemical analysis, spectral characterization by GC-MS followed by Molecular Docking of the characterized compound were performed. ADMET and DFT studies were carried out to select the suitability of drug compounds. Totally nineteen compounds were obtained and depending upon the highest mass percentage five compounds were selected. i) 6-Amino-1,2,3,4tetrahydroindan-5,7- Dione ii) 9, 12, 15 – Octadecatrienoicacid, methyl ester, iii) 1,2-Benzenedicarboxylic acid, butyl 2-methyl propyl ester iv) p-Decylphenoxsy acetic acid and v) 2,6,6-Trimethyl-2-3-[3-Oxo -3 – phenylpropenyl) cyclohexane for further studies. The selected five compounds qualified the Lipinski rule of five and were non – mutagenic and non – carcinogenic. Thus the compound p-Decylphenoxy acetic acid was found to be a potent and safe against HLA-DR4 associated with rheumatoid arthritis.